ENVIRONMENTAL ASSESSMENT STUDY BASED ON THE LIFE CYCLE OF SANJAICHIPS PRODUCTS IN PAYAKUMBUH, WEST SUMATERA - Nandar, Ramdani Hairul Nandar; Andes Ismayana; Yani, Moh (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
The growing productivity of the Sanjai chips agro-industry contributes to increasing emissions along the production process. This study aims to evaluate the environmental impact of Sanjai chips production using the Life Cycle Assessment (LCA) method. The assessment follows LCA stages: goal and scope definition, life cycle inventory, and impact assessment. The system boundary is gate-to-gate, focusing on the production stages: peeling, washing, slicing, frying, seasoning preparation (balado), mixing, and packaging. The functional unit is 1 kg of Sanjai chips. For each kilogram of product, inputs include 2.01 kg of cassava, 0.35 liters of cooking oil, 9.63 liters of water, and 2.61 kg of firewood, with 9.63 liters of wastewater produced. Environmental impacts were analyzed using SimaPro 9.4.2 software and the CML-IA Baseline method. Results show that 1 kg of Sanjai chips contributes to Global Warming Potential (GWP) of 1.3619 kg CO₂ eq, Acidification Potential (AP) of 0.0131 kg SO₂ eq, Eutrophication Potential (EP) of 0.0740 kg PO₄ eq, and Ozone Layer Depletion Potential (ODP) of 8.09E-07 kg CFC-11 eq. The frying stage is the primary hotspot, contributing 78.7% of total impacts, mainly due to cooking oil use. It is recommended that future research expand the system boundary to a cradle-to-grave scope and include social and economic dimensions to achieve a more holistic sustainability assessment. Keywords: environmental impact, life cycle assessment, sanjai chips, simapro